The telomere-to-telomere genome assembly and annotation of the rock carp (Procypris rabaudi) - Xiaolu Han; Xinle Li; Luohao Xu; Qi Liu; Shengqi Su; Weizhi Yao; Wenping He (Scientific Data)
Abstract Procypris rabaudi, commonly known as the rock carp, is an endemic economic fish in the middle-upper reaches of the Yangtze River. To enhance the understanding the biology of rack carps, a high-quality reference genome is required in different areas of study. Here, we generated the first telomere-to-telomere genome assembly and annotation of the rock carp, which spans 1.64 Gb with a contig N50 of 32.36 Mb. Hi-C assembly suggested that 99.83% sequences were positioned to 50 pseudo-chromosomes. Notably, 43 chromosomes were assembled without any gap. Through the integration of homologous-based predictions and RNA-sequencing technology, we identified 44,402 protein-coding genes, with 43,663 of them (98.3%) predicted to be functional. Furthermore, our assembled genome achieved 98.1% BUSCO completeness. This work improves the quality of the rock carp genome and provides valuable foundation for the future studies of genomics, biology and the fishery resources breeding.